Budaya sebagai Komoditas Streaming: Ekologi Media dan Komodifikasi Tradisi Indonesia dalam Film Netflix - Amalia Rizky Fatonah (JURNALISTIK DAN MEDIA, 2025)
This research explores how Indonesian culture is represented and commodified in locally produced Netflix films. Through an analysis of Guru-Guru Gokil (2020) and Nightmares and Daydreams (2024), the study examines how Indonesia’s social and spiritual values undergo a transformation of meaning within the digital media ecosystem. Employing a qualitative descriptive approach grounded in McLuhan’s Media Ecology Theory and Mosco’s Political Economy of Communication, this research reveals that Netflix functions not merely as a distribution platform, but as a global cultural environment that reconstructs the meaning of local culture to fit global market preferences. The commodification of culture occurs through aestheticization, simplification of meaning, and cultural datafication. Consequently, Indonesian culture in the streaming era emerges as a global entertainment product, representing local identity within the framework of platform capitalism..